Association between STAT3 gene Polymorphisms and Crohn’s disease susceptibility: a case–control study in a Chinese Han population - Wang, Zhengting (BioMed Central, 2014)
BACKGROUND: Crohn’s disease (CD) is an immune-related disease with genetic predisposition. This study aimed to investigate the association of three polymorphisms in the signal transducer and activator of transcription 3 (STAT3) gene with CD risk in a Chinese population. METHODS: We conducted a hospital-based case–control study involving 232 CD patients and 272 controls. Genotyping was performed using polymerase chain reaction with sequence-specific primer method. Statistical analyses were conducted using logistic regression and genotype risk scoring. RESULTS: Significant differences were found between patients and controls in allele/genotype distributions of rs744166 (Pallele = 0.0008; Pgenotype = 0.003) and allele distributions of rs4796793 (P = 0.03). The risk for CD associated with the rs744166-A mutant allele decreased by 37% [95% confidence interval (CI): 0.48–0.83] under the additive model, 39% (95% CI: 0.43–0.81) under the dominant model and 57% (95% CI: 0.24–0.77) under the recessive model. Carriers of the rs4796793-G mutant allele exhibited 25% (95% CI: 0.58–0.98; P = 0.03) and 47% (95% CI: 0.30–0.95) decreased risks of developing CD under the additive and recessive models, respectively. CONCLUSIONS: STAT3 rs744166 and rs4796793 polymorphisms may be associated with CD occurrence and used as a predictive factor of CD in Chinese Han populations. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://diagnosticpathology.slidepath.com/webViewer.php?snapshotId=1297687014